PENGARUH METODE DRILL TERHADAP TINGKAT KEJENUHAN PESERTA EKSTRAKURIKULER BOLA VOLI DI SMP NEGERI 1 KERTASEMAYA INDRAMAYU - Ricky Subagja; Udi Sahudi (JOURNAL RESPECS, 2019)
Ricky Subagja dan Udi Sahudi Pendidikan Jasmani, Universitas Majalengka rickysubagja885@gmail.com ABSTRACT This research was conducted to determine the effect of the drill method on the saturation level of volleyball extracurricular participants in state junior high school 1 paper. and of these 30 samples were students who took volleyball extracurricular activities, and then were treated for 12 meetings. The instrument in this study was to use a questionnaire with a Likert measurement scale with data processing techniques using validity test, reliability test and t test. The results of this study indicate that the application of the drill method to the saturation level of volleyball extracurricular participants has an effect on decreasing students' boredom with basic volleyball technique with a calculated value for student saturation is 12,350 with probability Sig. (2-tailed) 0,000. Because the probability is Sig. (2-tailed) 0,000